Rancang Bangun Aplikasi Sistem Informasi Manajemen Laboratorium Biomedik Fakultas Kedokteran Universitas Brawijaya - Ahmad Leo Yudanto; Herman Tolle; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Biomedical Laboratory is one of laboratories at Brawijaya University Medical Faculty. Considering the eminent level of requirement for laboratory's various services management which continues to grow along with the need for a data inventory and monitoring of materials and equipment stock, it is necessary to rebuilt laboratory management information system to facilitate every laboratory requirements while providing simplicity and flexibility for future development. Biomedical laboratory management information system has to be redesigned according to user requirements based on comprehensive requirements analysis phase with detailed design so it can be completely implemented and in accordance with user requirements. This technologies are Laravel 5 framework which built by PHP programming language and Apache server as a local server which would be installed on several computers at laboratory. This research produces an information system which can perform data inventory process, stock monitoring of materials and tools and also informations system alreadys meet laboratorium's business process and functionality requirement that already have been tested by software testing method.